Neurofibrillary changes undergoing morphological and biochemical changes – How does tau with the profile shift of from four repeat to three repeat spread in Alzheimer brain?. Issue 5 (22nd July 2020) - Uchihara, Toshiki
Abstract : The concept of the hierarchal spread of neurofibrillary tangles (NFTs) from the hippocampus to the cortex in Alzheimer's disease (AD)/aging brains, initially proposed by Braak and Braak, revolutionized our understanding by putatively explaining that tau lesions are being unidirectionally extended along neural connections. Because pathological misfolding of tau can serve as a seed to induce identical misfolding on normal tau, this prion‐like property is considered to represent a molecular mechanism that may explain such lesion spread. However, double labeling studies for three repeat (3R) and four repeat (4R) tau demonstrated a profile shift in these tau isoforms along chronological change: initially positive only for 4R in early pretangles, gradual involvement of 3R in mature NFTs, and finally replaced by 3R in advanced ghost tangles. This profile shift is hardly explained by aggregation of a single tau molecule. Surprisingly, this profile shift from 4R to 3R tau is shared with the hierarchal spread of NFT around the hippocampus, which is hardly explained by a simple mechanism such as propagation of a single tau molecule. Some molecules other than tau or non‐materialist influences such as neuronal activity may be candidate mechanisms to explain this regional profile shift if it is mediated by neural connections. Because this profile shift is shared with brainstem NFTs, it may instead represent a cell autonomous phenomenon, tightly linked with progression of AD but not necessarily linked with prion‐like propagation along neural connections. In addition, we recently clarified that posttranslational deamidation of 4R tau at asparagine 279 to aspartate is a marker for AD, distinct from progressive supranuclear palsy (PSP)/corticobasal degeneration (CBD). This may provide another axis to see how AD‐NFTs develop and how their 4R tau is distinct from 4R tau of PSP/CBD. Because tau species and their distributions are disease‐specific, molecular homogenization, such as "tauopathy" to encompass AD, PSP/CBD and Pick body disease, is just an oversimplification that may obscure fundamental distinctions between human diseases. Careful reference to the realities of human brain disease may provide a solid and fruitful basis to improve diagnostic and therapeutic strategies to tackle these intractable diseases.